2021
DOI: 10.1007/s00430-020-00698-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two rapid antigen tests to detect SARS-CoV-2 in a hospital setting

Abstract: Successful containment strategies for the SARS-CoV-2 pandemic will depend on reliable diagnostic assays. Point-of-care antigen tests (POCT) may provide an alternative to time-consuming PCR tests to rapidly screen for acute infections on site. Here, we evaluated two SARS-CoV-2 antigen tests: the STANDARD™ F COVID-19 Ag FIA (FIA) and the SARS-CoV-2 Rapid Antigen Test (RAT). For diagnostic assessment, we used a large set of PCR-positive and PCR-negative respiratory swabs from asymptomatic and symptomatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 13 publications
6
57
1
3
Order By: Relevance
“…Finally, the Ag-RDT RDT BIOSYNEX COVID-19 Ag BSS ful lled the current WHO's recommendations for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify signi cantly more cases than they would miss (sensitivity ≥ 80%) and would have very high speci city (≥ 97-100%) [20]. Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral ow immunoassay format [7,9,21,[25][26][27][28][29][30][31][32][33][34][35], while several studies have reported much lower sensitivity levels contrasting with always high speci city [3,[36][37][38][39][40][41]. For example, a comparable Ag-RDT such as the novel COVID-VIRO® from AAZ (Boulogne Billancourt, France) showed a sensitivity of 96.7% and a speci city of 100% in a real-life community setting [31].…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the Ag-RDT RDT BIOSYNEX COVID-19 Ag BSS ful lled the current WHO's recommendations for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify signi cantly more cases than they would miss (sensitivity ≥ 80%) and would have very high speci city (≥ 97-100%) [20]. Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral ow immunoassay format [7,9,21,[25][26][27][28][29][30][31][32][33][34][35], while several studies have reported much lower sensitivity levels contrasting with always high speci city [3,[36][37][38][39][40][41]. For example, a comparable Ag-RDT such as the novel COVID-VIRO® from AAZ (Boulogne Billancourt, France) showed a sensitivity of 96.7% and a speci city of 100% in a real-life community setting [31].…”
Section: Discussionsupporting
confidence: 83%
“…The study Ag-RDT fulfilled the current World Health Organization (WHO)'s recommendations for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify significantly more cases than they would miss (sensitivity !80%) and would have very high specificity (!97-100%) (World Health Organization, 2020a). Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral flow immunoassay format (Cerutti et al, 2020;Chaimayo et al, 2020;Diao et al, 2021;Favresse et al, 2021;Linares et al, 2020;Schildgen et al, 2021;Toptan et al, 2020;Weitzel et al, 2020), while several studies have reported much lower sensitivity levels contrasting with always high specificity (Albert et al, 2020;Dinnes et al, 2020;Scohy et al, 2020;Yamayoshi et al, 2020;Osterman et al, 2021;Torres et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Studies that show lower sensitivity on either of the two tests (e.g. 64.5% by Osterman et al [ 14 ] for Roche SARS-CoV-2 Ag-RDT or Olearo et al [ 15 ] with 44.6% for Panbio in symptomatic patients), most commonly perform the test not according to manufacturer’s recommendations (most often either not using the sample type or swab recommended, or prediluting the sample in transport media). This possible reason for the difference in performance between studies was also highlighted in the recent systematic reviews.…”
Section: Discussionmentioning
confidence: 99%